2020
DOI: 10.1002/ptr.6859
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract supplementation along with a restricted‐calorie diet improves cardiovascular risk factors in obese or overweight adult individuals: A randomized, placebo‐controlled trial

Abstract: Grape seed extract (GSE) is a flavonoid‐rich supplement, recently discussed as a potential moderator of inflammation and obesity. In this study, we aimed to investigate the effects of GSE supplementation along with a restricted‐calorie diet (RCD), on changes in blood lipid profile, visceral adiposity index (VAI), and atherogenic index of plasma (AIP). We designed a randomized, double‐blinded, placebo‐controlled clinical trial. Forty obese or overweight individuals (25 ≤ body mass index < 40 kg/m2) were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…The effect of intervention with either grape seed or bilberry and blackcurrant extract on HDL cholesterol was more variable. Only one study with grape seed extract [ 35 ], and three intervention studies with bilberry and blackcurrant extract [ 30 , 33 , 43 ], showed a significant average increase in HDL cholesterol, but the response was not linked to study design or population characteristics, or other study outcomes. Dose did not affect the response in cholesterol levels ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of intervention with either grape seed or bilberry and blackcurrant extract on HDL cholesterol was more variable. Only one study with grape seed extract [ 35 ], and three intervention studies with bilberry and blackcurrant extract [ 30 , 33 , 43 ], showed a significant average increase in HDL cholesterol, but the response was not linked to study design or population characteristics, or other study outcomes. Dose did not affect the response in cholesterol levels ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies-sixteen studies with grape seed extract and four studies with berry and blackcurrant extract-measured effects on cholesterol outcomes. All four berry and blackcurrant extract studies [30,33,41,43] and five of the sixteen grape seed tract studies [26][27][28][29]35] observed significant improvements in at least one choles marker. Significant reductions in total and LDL cholesterol were observed across stu and in different study populations where subjects had been diagnosed with hyperch terolemia, T2DM or metabolic syndrome, in those studies that lasted four weeks or lon Longer study durations did not reduce total and LDL cholesterol further.…”
Section: Efficacy Of Grape Seed or Bilberry And Blackcurrant Extract Supplements To Modulate C Lesterol Metabolismmentioning
confidence: 99%
“…Polyphenols-rich grape extract capsules (300 mg/day) were orally given to obese individuals for a period of 12 weeks. The results predicted that grape extracts decreased the plasma LDL-C level from 131 ± 4.98 to 110.28 ± 5.8 mg/dl [80]. Luteolin, a bioactive compound present in chrysanthemum, was evaluated for its LDL-C lowering effect on hyperlipidemia rats.…”
Section: Dietary Polyphenols: Potential Ldl-c Lowering Agentsmentioning
confidence: 99%
“…A total of 12 of the 36 included studies were randomized controlled trials [33,34,37,41,43,50,56,57,[59][60][61]67], 8 were cross-sectional studies [36,39,40,44,45,49,51,58], 6 were prospective cohort studies [32,47,55,[63][64][65], 4 were cohort studies [46,52,62,66], 2 were crossover studies [38,53], 2 were randomized non-controlled trials [35,42], and 2 were prospective non-randomized: pre/post studies [48,54]. Telomere length (TL) was measured using saliva samples and ultra-processed food (UPF) consumption was collected using a validated 136-item food frequency questionnaire (FFQ); the association between consumption of energy-adjusted UPF and the risk of having short telomeres was evaluated using logistic regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty two of the thirty-six included studies examined the results based on the adult population [32,33,[35][36][37]40,[46][47][48][49][52][53][54][55][57][58][59][60]63,64,66,67] and fourteen only recruited older adults [34,38,39,[41][42][43][44][45]50,51,56,61,62,65].…”
Section: Sample Size and Study Populationmentioning
confidence: 99%